Intravascular Polarimetry: Clinical Translation and Future Applications of Catheter-Based Polarization Sensitive Optical Frequency Domain Imaging - Otsuka, Kenichiro; Villiger, Martin; Nadkarni, Seemantini K.; Bouma, Brett E. (Frontiers in Cardiovascular Medicine, 2020)
Optical coherence tomography (OCT) and optical frequency domain imaging (OFDI) visualize the coronary artery wall and plaque morphology in great detail. The advent of these high-resolution intracoronary imaging modalities has propelled our understanding of coronary atherosclerosis and provided enhanced guidance for percutaneous coronary intervention. Yet, the lack of contrast between distinct tissue types and plaque compositions impedes further elucidation of the complex mechanisms that contribute to acute coronary syndrome (ACS) and hinders the prospective identification of plaques susceptible to rupture. Intravascular polarimetry with polarization-sensitive OFDI measures polarization properties of the coronary arterial wall using conventional intravascular imaging catheters. The quantitative polarization metrics display notable image contrast between several relevant coronary plaque microstructures that are difficult to identify with conventional OCT and OFDI. Tissues rich in collagen and smooth muscle cells exhibit birefringence, while lipid and macrophages cause depolarization. In this review, we describe the basic principles of intravascular polarimetry, discuss the interpretation of the polarization signatures, and outline promising avenues for future research and clinical implications.